Optimizing the Placement of Ground Support Equipment in the Equipment Parking Area on the Level of Smooth Operations on the Air Side of Halim Perdana Kusuma International Airport - Suryadi, Kakang Kapela; Yudianto, Kifni (CV. Rayyan Dwi Bharata, 2024)
In this case, to facilitate operational activities on the air side, especially the apron, there is one unit, namely Ground Support Equipment (GSE), which functions as a tool that is prepared for aircraft needs on the ground during departure and arrival, loading and unloading of goods and cargo, post, as well as boarding and descending passengers. Fluency can encourage activities or activities that will be carried out by someone so that it will have an effect on maximum results and as desired. However, in the GSE unit there are still obstacles which result in operational activities on the air side not running smoothly.This research uses qualitative methods with data collection techniques by conducting interviews, observation and documentation. Interviews were conducted with 3 sources from Apron Movement Control (AMC) officers at Halim Perdana Kusuma International Airport. The results of this research indicate that the placement of each Ground Support Equipment (GSE) is still not optimal at Halim Perdana Kusuma Airport because there are still many in the form of Motorized and Non-Motorized whose placement is combined as a whole in one Equipment Parking Area (EPA) but there are some that have been placed in accordance with the placement contract in the Equipment Parking Area (EPA).